Ḥadīṡ- ḥadīṡ Bermasalah (Studi Atas Pemikiran Ali Mustafa Yaqub Dan Nur Hidayat Muhammad) - Harahap, Alwi Padly (SHAHIH (Jurnal Ilmu Kewahyuan), 2023)
This research is entitled Problematic Ḥadīṡ-Ḥadīṡ which specifically discusses the thoughts of Ali Mustafa Yaqub and Nur Hidayat Muhammad. The background for choosing this object is to find out the thoughts of the two figures studied regarding the methods they use in identifying a ḥadīṡ. Judging from the results of research conducted by the two figures studied, it appears that the two figures have different perspectives through the approach used in identifying a ḥadīṡ. This study uses a qualitative approach, muqaranah, with data collection techniques through interviews, observation and document studies. Data analysis was carried out to produce an understandable understanding. The knowledge inherited from the two figures studied can be seen through the works of books, especially those related to the ḥadīṡ of the Prophet. The results of this study will: Knowing the methods used by Ali Mustafa Yaqub and Nur Hidayat Muhammad in identifying and verifying problematic ḥadīṡ-ḥadīṡ, and knowing the similarities and differences between the two figures.